Co9Se8 nanoparticles as high capacity anode material for lithium-ion batteries - Kumar, Pushpendra; Hu, Lung-Hao (Materials Research Express, 2018)
Present investigation deal with the facile synthesis of Co9Se8 nanoparticles (NPs) and their application as the potential anode for lithium-ion battery (LIB). The primary size of the Co9Se8 NPs can be achieved between 10 similar to 25 nm while the secondary cluster size ranging from 150 similar to 200 nm as observed by transmission electron microscope (TEM). The specific capacity of Co9Se8 NPs LIB anode can reach around similar to 610 mAhg(-1) during charging (lithium ion released from Co9Se8 nanoparticles), and -730 mAhg(-1) during discharging (lithium ion intercalated) at an applied current density of similar to 100 mAg(-1). These values are significantly higher than that of the commercial graphite anode (theoretical capacity similar to 372 mAhg(-1)). The irreversibility of Co9Se8 anode (similar to 15%) is also significantly lower than that of most metal oxides and silicon-based anodes (irreversibility ranging between 30 similar to 50% or higher for Si). The reason for superior specific capacity and low irreversibility compared to metal oxides and silicon-based materials could be owing to the stable nano-cluster size which help to reduce the diffusion path and internal resistance to lithium ion.
Keywords: irreversibility; lithium-ion battery; lithium-ion diffusion; Nanoparticles; specific capacity

MoSx surface-modified, hybrid core-shell structured LiFePO4 cathode for superior Li-ion battery applications - Hu, Lung-Hao; Kumar, Pushpendra (Journal of Alloys and Compounds, 2021)
A hybrid core-shell cathode, composed of MoSx shell and carbon-coated lithium iron phosphate core (MoSx@cLiFePO(4) or MoSx@c-LFP) is obtained by the post-annealing of a thermally decomposable ammonium thiomolybdate and commercial carbon-coated LiFePO4 (c-LFP) powder. The specific capacity of the commercially available amorphous carbon-coated LFP (c-LFP) is typically around 120-160 mAhg(-1), which is usually lower than the theoretical values similar to 170 mAhg(-1) due to the limited Li+ phase-boundary diffusion and low electrical conductivity. In the present investigation, we report that the specific capacity of surfacemodified (similar to 1.2 wt% of layered MoSx) c-LFP (MoSx@c-LFP) material can reach as high as similar to 228 mAhg(-1) delivering high gravimetric energy density similar to 750-770 Whkg(-1). The excess capacity can be attributed to the partial Li-ions intercalated/de-intercalated through the MoSx layers within a specific potential range (2.0-3.8 V). MoSx coating helps increase the c-LFP surface's stability by forming strong covalent bonding and is believed to enhance the electronic conduction by reducing the interparticle contact. During charge and discharge the hysteresis is substantially reduced by MoSx coating. The approach may open up a universal route to increase the cathode capacity, potentially attractive for further Li-ion battery research and industrial applications. (C) 2021 Elsevier B.V. All rights reserved.
Keywords: Ammonium thiomolybdate; Coulombic efficiency; Hybrid core-shell cathode; hysteresis; MoSx